Treatment Responsiveness in CIDP Patients with Diabetes Is Associated with Higher Degrees of Demyelination - Abraham, Alon (PLoS One, 2015)
INTRODUCTION: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is one of several chronic treatable acquired demyelinating neuropathies. OBJECTIVES: To explore the association between the degree of demyelination in CIDP, and treatment responsiveness. METHODS: A retrospective chart review of CIDP subjects assessed between 1997 and 2013 was performed to compare treatment responsiveness using different sets of criteria. RESULTS: 99 CIDP patients were included, 34 with diabetes mellitus (DM). Treatment responsiveness was higher in CIDP-DM fulfilling 1 or more EFNS/PNS criteria, (63% vs. 31%, p = 0.03), and in CIDP+DM fulfilling 2 or more criteria (89% vs. 36%, p = 0.01). Nonetheless, treatment responsiveness in CIDP+DM had the highest odds ratio (3.73, p = 0.01). Similar results were also shown in simplified uniform study criteria, with 10% cut off values for CIDP-DM, compared to 30% for CIDP+DM. CONCLUSION: In CIDP+DM, higher degrees of demyelination are associated with treatment responsiveness, implying the need to adjust current criteria in these patients.